Manganese(II) complexes of hydrazone based NNO-donor ligands and their catalytic activity in the oxidation of olefins. Issue 5 (4th March 2017) - Bikas, Rahman; Ghorbanloo, Massomeh; Sasani, Roya; Pantenburg, Ingo; Meyer, Gerd
Abstract: The reaction between tridentate NNO donor hydrazone ligands, ( E )-2-cyano- N′ -(phenyl(pyridin-2-yl)methylene)acetohydrazide (HL 1 ) and ( E )-2-cyano- N′ -(1-(pyridin-2-yl)ethylidene)acetohydrazide (HL 2 ), with MnCl2 ·4H2 O in methanol resulted in [Mn(HL 1 )Cl2 (CH3 OH)] (1 ) and [Mn(HL 2 )Cl2 (CH3 OH)] (2 ). Molecular structures of the complexes were determined by single-crystal X-ray diffraction. All of the investigated compounds were further characterized by elemental analysis, FT-IR, TGA, and UV–Vis spectroscopy. These complexes were used as catalysts for olefin oxidation in the presence of tert -butylhydroperoxide (TBHP) as an oxidant. Under similar experimental conditions with equal manganese loading, the presence of [Mn(HL 2 )Cl2 (CH3 OH)] (2 ) resulted in higher conversion than [Mn(HL 1 )Cl2 (CH3 OH)] (1 ). Abstract :